Ileo-colic intussusception in an adolescent secondary to high-grade B-cell (Burkitt’s) lymphoma: a case report and literature review - Kumar, Supreet; Bhalerao, Aishwarya S.; Shah, Suryalok P.; Pandey, Alok K.; Tandon, Vivek; Govil, Deepak (International Surgery Journal, 2025)
Intussusception in older children and adolescents is relatively uncommon and is frequently associated with a pathological lead point. High-grade B-cell lymphomas (e.g., Burkitt lymphoma) may involve the abdomen and precipitate intussusception. A 16-year-old male presented with a two-week history of intermittent upper abdominal pain, melena, and symptomatic anemia. Contrast-enhanced computed tomography (CECT) demonstrated ileo-colic intussusception. Exploratory laparotomy revealed a polypoidal mass in the ascending colon acting as the lead point, necessitating a right hemicolectomy. Histopathological and immunohistochemical analyses confirmed high-grade B-cell lymphoma consistent with Burkitt lymphoma. The patient’s postoperative course was uneventful, and he was referred for chemotherapy. This case underscores the importance of considering Burkitt lymphoma in adolescent patients with intussusception. Prompt surgical intervention, definitive histopathological confirmation, and timely initiation of chemotherapy are critical to optimizing patient outcomes.